International Open Access Week 2018: chronicle of activities (Confluenţe Bibliologice, 2018)
In the Scientific Library USARB was promoted the 11th time the International Open Access Week to Information. The university librarians participated in this Week offering a range of open access activities and services that supported the theme “DESIGNING EQUITABLE FOUNDATIONS FOR OPEN KNOWLEDGE“. 22 librarians connected over 500 users to this event: teachers, master students, students. On Science Day (October 24), announced by the REM Consortium, librarians presented over 100 databases subscribed by the USARB, including the Cambridge Journals Online information products; Taylor & Francis Online Journal Library; Web of Science, access to these resources can be funded under the project “Modernization of academic library servicesin Moldova”.
Keywords: databases; Open Access Week